(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Patients with abnormalities of thyroid gland function or structure come to medical attention for several reasons. They present with symptoms attributable to physiologic effects of increased or decreased plasma concentrations of thyroid hormone (hyperthyroidism or hypothyroidism, respectively). They may also present with symptoms related to localized or generalized enlargement of the gland (diffuse goiter, multinodular goiter, or single thyroid nodule).